(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The principles of soil science and agrochemistry are used to maintain and increase soil fertility and to provide cotton with mineral nutrition on a scientific basis. The main problems in cotton growing are: ecological problems and environmental protection, soil fertility, wind and water erosion, labor productivity and the efficiency of all agrotechnical measures in the field; increasing cotton yield; improving product quality are among the urgent issues.